Pengaruh Promosi dan Harga terhadap Keputusan Pembelian Mobil Suzuki Pada PT. Surya Batara Mahkota (SBM) Maumere: (Studi Kasus Pada Konsumen PT. Surya Batara Mahkota (SBM) Maumere) - Bertolomeus Wara Meto; Yoseph D. P. Rangga; Nunsio H. Meylano (Jurnal CUAN Universitas Nusa Nipa Maumere, 2024)
This research aims to: (1) determine the description of promotions, prices, and purchasing decisions at PT. Suria Batara Mahkota (SBM) Maumere (2) determine whether promotions and prices affect purchasing decisions at PT. Suria Batara Mahkota (SBM)Maumere. The population in this research was the consumers who bought Suzuki cars in 2023 from PT Surya Batara Mahkota (SBM). According to sales data, there were 118 car sales in 2023. The descriptive analysis indicated the promotion variable (X1) and the price variable (X2) both fall into the "good" category, as does the purchasing decision variable (Y). Furthermore, the t-test hypothesis analysis showed the promotion variable (X1) had a significant effect on the purchasing decision variable (Y), while the price variable (X2) only partially affected the purchasing decision variable (Y). The F-test statistics revealed that both independent variables, promotion (X1) and price (X2), had a signifcant combined effect on the purchasing decision (Y). Finally, the determination analysis demonstrated the contribution of the promotion and price variables to the purchase decision of Suzuki cars at PT. Surya Batara Mahkota (SBM) Maumere is 34.8%, while the remaining 65.2% is influenced by factors outside the scope of the research.